Sektor Transportasi pada Angkutan Barang dalam Pertumbuhan Ekonomi di Indonesia - Arum Dhista Ayunia; Nofrisel Nofrisel; I Made Adnyana (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of the study is to obtain empirical evidence about the impact between Freight Volume and Growth Domestic Product in Indonesia using time series data from 2008 to 2018. The Freight Volume data (using train or rail, sea, and air) as the logistics variable and Growth Domestic Product (GDP) as the variable of economic growth. The study was using the analysis of Simple Linear Regression. The results are (a) the rail freight volume has positive and significant effect on GDP of 0,835 or 83,5% and 16,5% are from other unexamined factors, (b) the sea freight volume has no impact on GDP of 0,444 or 44,4% and 55,6% are from other unexamined factors, and (c) the air freight volume has positive and significant effect on GDP of 0,580 or 58% and 42% from other unexamined factors.